History of invasion of water bodies in northwestern Russia by amphipods Gmelinoides fasciatus (Crustacea) - Sidorova A.I. (Трансформация экосистем)
The summarized literature and our own data on spread of the invasive species Gmelinoides fasciatus (Stebbing, 1899) (Crustacea: Amphipoda) in water bodies of northwestern Russia, as well as the chronology of its introduction and invasive corridors for the past 60 years (1962–2022) are presented. G. fasciatus began to settle upstream and downstream along the river system after its intentional introduction into the Gorky Reservoir and water bodies of Leningrad Oblast to increase food supply for fish. Currently, this amphipod is recorded in the littoral zone of the largest water bodies of Europe (lakes Ladoga and Onega) and in the easternmost part of the Gulf of Finland. The obtained scenario of G. fasciatus invasion can be used in predicting dispersion of another Baikal invader (Micruropus possolskii Sowinsky, 1915), which actively colonizes the shallow areas in the southwestern part of Lake Ladoga and is able to expand its habitat under favorable temperature and hydrochemical conditions.